Problem of software synthesis from made-up components - Giedrimas, Vaidas (Lietuvos matematikos rinkinys, 2003)
The paper analyze software synthesis from components problem, overviews possible solutions. This article shows that synthesis of programs (SSP) is suitable method to solve this problem.